2007
DOI: 10.1007/s11418-006-0108-5
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxic effect of nordihydroguaiaretic acid against chlormadinone acetate-induced genotoxicity in mice bone-marrow cells

Abstract: Nordihydroguaiaretic acid (NDGA), a phenolic lignan, was tested for its antigenotoxic potential against chlormadinone acetate (CMA)-induced genotoxic damage in mice bone-marrow cells. Doses of about 22.50 mg/kg body weight of CMA were given along with 1, 5 and 10 mg/kg body weight of NDGA intraperitoneally. The treatment resulted in the reduction of sister chromatid exchanges and chromosomal aberrations induced by CMA, suggesting an antigenotoxic potential of NDGA. Earlier studies show that CMA generates react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In fact, Nikolic et al [41] reported that plant terpenes exhibited antigenotoxic activty. On the other hand Siddique et al [42] demonstrated that a phenolic lignan (nordihydroguaiaretic acid), possesses an antigenotoxic potential against chlormadinone acetate induced genotoxic damage in mice bone-marrow cells.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Nikolic et al [41] reported that plant terpenes exhibited antigenotoxic activty. On the other hand Siddique et al [42] demonstrated that a phenolic lignan (nordihydroguaiaretic acid), possesses an antigenotoxic potential against chlormadinone acetate induced genotoxic damage in mice bone-marrow cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is also thought that the decrease in the total number of individuals of D. melanogaster subject to applications of CMA at different concentrations is a result of the genotoxic effect of CMA. Sidduge et al, (2008) have determined that CMA has genotoxic and cytotoxic effects on bone marrow of mice and that these effects can be eliminated by the scavenging effect of NDGA on hydroxyl radicals, superoxide anions, singlet oxygen and hypochlorous acids (Siddique et al, 2008). With such features NDGA is accepted as a powerful antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged use of estrogens has been reported to develop various types of malignancies in human and experimental animals [15]. The genotoxic effects of estrogens/ proges tins can be reduced by the use of antioxidants [16][17][18][19][20][21][22] and natural plant products [23][24][25][26][27][28]. The genotoxicity testing provides human a risk assessment.…”
Section: Introductionmentioning
confidence: 99%